Decoding international law semiotics and the humanities - Tiefenbrun, Susan W. (New York ; Oxford : Oxford University Press, 2010)
Violations of international law and human rights laws are the plague of the 20th and 21st centuries. People's inhumanity to people escalates as wars proliferate and respect for human rights and the laws of war diminish. Decoding International Law analyses international law as represented artfully in the humanities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Semiotics (Law); Civil rights; International law; Culture -- Semiotic models